Feminisasi Nila (GIFT), Oreochromis sp. Menggunakan Hormon Estradiol 17-β - Titin Kurniasih; Otong Zenal Arifin; Marizal Marizal (Universitas Gadjah Mada, 2006)
Research to find out the effect of oral administration of estradiol 17-β on feminization of Oreochromis sp. (GIFT) fry was carried out at Cibalagung Research Station. Five different concentrations of estradiol 17-β i.e.: 60, 80, 100, 120 and 0 mg/kg feed, were given to larvae of 6 days old twice a day for 21 days in triplicates. The result indicated that there was significant difference of average percentage of female between control and treatments.The highest percentage of female was obtained from fish treated with 100 mg estradiol /kg feed (86.6%), whereas the lowest was obtained from fish control (51.7%). The survival rate and length growth were not significantly different. Survival rate of larvae ranged from 94 to 97.7% and the average of length growth ranged from 10.08 to 13.32 mm.